Studi Mendalam Bentuk-Bentuk Diskriminasi Gender Dalam Novel The Handmaid’s Tale Karya Margaret Atwood - Pratiwi, Dina (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2024)
Discrimination is often directed at groups or individuals based on attributes they cannot change, such as gender, race, religion, sexual orientation, or social status. Gender discrimination is one of the social issues that has become a major concern in various fields of study, including in the field of literature. This study aims to analyze and identify various forms of gender discrimination in the novel The Handmaid's Tale by Margaret Atwood. The research method used is qualitative-descriptive with an objective approach. The data collection technique is carried out through reading and recording techniques. The results of the analysis show that gender discrimination in this novel can be identified in five main forms: marginalization, subordination, stereotyping, violence, and double burden. Marginalization can be seen through the treatment of women as objects of reproduction, subordination through power hierarchies that place women in a lower position, stereotypes through derogatory views of women's abilities, violence through physical and psychological control, and double burdens through the dual roles that women must play without adequate support. This research provides insight into the social and cultural dynamics that affect women's lives, as well as increasing public awareness of gender issues that are often hidden in daily life.